Indoor global path planning based on critical cells using dijkstra algorithm - Azrul Amri, Jamal; Engku Fadzli Hasan, Syed Abdullah; Fatma Susilawati, Mohamad (Asian Research Publishing Network, 2015)
Path planning has been implemented in various robotics systems, and the results checked. This paper proposes global path planning based on grids representation in an indoor environment using Dijkstra algorithm. The algorithm uses floor plan of any environment discretized to some equal-sized square grids. Cells that contained doorways, corner, curve and junction are considered as critical cells. These critical cells are used as the vertices to the Dijkstra algorithm, with distances between two successive cells as edges between them, and the shortest path between a set of predefined points within the terrain can then be calculated. Simulations results show that the proposed algorithm enhances performance and speed compared to the traditional Dijkstra’s algorithm.